1429. Meningococcal Disease Outbreak in a Refugee Reception Identification Center in Greece and Administration of Mass Antibiotic Prophylaxis. (31st December 2020) - Magaziotou, Ioanna; Tsiodras, Sotirios; Xirogianni, Athanasia; Tseroni, Maria; Syrigonaki, Katerina; Stoli, Artemis; Tsekou, Aikaterini; Papandreou, Anastasia; Sapounas, Spyros; Panagiotakopoulos, George; Theodoridou, Maria; Tzanakaki, Georgina; et al.
Abstract: Background: An increased likelihood of transmission of communicable diseases such as invasive meningococcal disease (IMD) exists in refugee camps. Herein, we describe an outbreak investigation of 5 IMD cases among immigrants in Greece. Methods: Epidemiological, clinical and laboratory data (culture and molecular identification) as well as the public health management concerning an outbreak of meningococcal disease in a refugee Reception Identification Center (RIC), are described. Results: During the period 17 th January - 17 th February 2020, five cases of IMD in refugees were reported to the National Public Health Organization (NPHO). Four cases were from Afghanistan and resided in the RIC of Lesvos Island; two females aged 2 yo and 21 yo and two males 13 yo and 6 yo. The fifth case, a 4 month old male of Syrian nationality, exhibited symptoms after moving to an inland accommodation center (AC) from Lesvos RIC, on December 2019. Four of the cases presented with meningitis and septicaemia. All cases recovered and had no common exposure other than shared geographic space. Neisseria meningitidis was identified by molecular typing (mPCR, PorA, MLST, WGS) in all cases at the National Meningitis Reference Laboratory; 3/5 cases were identified as MenB, porA 7-2, 4, and ST-3129 (new clone) while 2/5 (21 yo female, 13 yo male) as MenY, porA: 5.2, ST-22cc. To prevent secondary cases, antimicrobial chemoprophylaxis via Directly Observed Therapy (DOT) was administered to 4.024 Afgan close contacts (26.7% of the total Afgan population). MenACWY and MenB vaccination was recommended in response to outbreak among persons aged < 20 years old. No new IMD case occurred in the RIC during a follow-up period of 4 months. Conclusion: The detection of a new clone in Greece of Chinese and Taiwanese origin through migrants, further underlines the need of enhanced surveillance for early detection, molecular typing, immediate intervention with antibiotic prophylaxis and/or supplemental vaccination in order to prevent IMD in refugee camps. Disclosures: All Authors : No reported disclosures